Postoperative Inflammation After Endoscopic Cyclophotocoagulation: Racial Distribution and Effect on Outcomes. Issue 3 (March 2018) - Edmiston, Anna M.; SooHoo, Jeffrey R.; Seibold, Leonard K.; Kahook, Malik Y.; Palestine, Alan G.; Pantcheva, Mina B.
Abstract : Purpose: To assess the prevalence of postoperative anterior chamber reaction or persistent anterior uveitis (PAU) by race and its effect on intraocular pressure (IOP) and visual acuity (VA) after combined phacoemulsification and endoscopic cyclophotocoagulation (ECP) in primary open-angle glaucoma. Patients and Methods: A retrospective analysis of all patients with primary open-angle glaucoma who underwent combined phacoemulsification cataract extraction with ECP from January 1, 2007 to October 31, 2015. VA, IOP, presence of anterior chamber cells, steroid treatment, and number of IOP lowering drops were analyzed preoperatively and up to 3 months postoperatively. Patients were categorized according to self-reported race. PAU was treated according to severity and presence of symptoms. Results: Two hundred twenty-three eyes met the inclusion criteria. PAU was present in 22.4% of eyes. PAU was significantly correlated with race, particularly African American race. PAU was also associated with a lack of improvement in inflammation at week 1 compared with day 1 postoperatively. However, there was no significant difference in VA, IOP, or reduction of IOP lowering drops in those with or without PAU. When comparing African Americans to whites, PAU and its treatment were not associated with a difference in IOP reduction at 3 months. Conclusions: PAU is common after combined phacoemulsification and ECP and is significantly correlated with race. Although PAU may require prolonged postoperative treatment, our data does not support poorer VA or IOP outcomes.